ENGLISH IS FUN: AN ENGLISH LANGUAGE USR PROJECT TO STIMULATE YOUNG MINDS - Syazliyati Ibrahim; Berlian Nur Morat; Robekhah Harun; Norlizawati Md Tahir; Zawani Badri; Rafidah Amat (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
Corporate social responsibility is presently in currency at various higher education institutions and is known as university social responsibility or USR. This is relevant to the government’s aspiration in attempting to close the gap between universities and communities. One of the efforts taken to get closer to the community was by reaching out to establishments offering preschool education to young learners. The project was named English is Fun and is designed to cater to young learners. This project was voluntarily conducted by a group of English language lecturers and a designer at kindergartens in the neighbouring area. The project involved preschool students; organised as a half-day activity, requiring the students to complete a created puzzle on human body parts. Questionnaire surveys were given to the students who joined the activities, and they gave positive feedback. In the future, the efforts can be expanded with other activities at the same preschool establishment or similar activities can be conducted at other kindergartens in other areas. Either way, the bottom line is universities should give back to the communities by offering voluntary services that are practical, easy to execute and also economical.